Application of CRISPR/Cas9 to edit genes affecting seed morphology traits in wheat - Pan, Qianli (Kansas State University, 2019)
The CRISPR/Cas9-based genome editing system holds a great promise to accelerate wheat improvement by helping us to understand the molecular basis of agronomic traits and providing means to modify genes controlling these traits. CRISPR/Cas9 is based on a synthetic guide-RNA (gRNA) that can guide Cas9 nuclease to specific targets in the genome and create double strand breaks (DSB). The DSB are repaired through the error-prone non-homologous end joining process causing insertions or deletions that may result in loss-of-function mutations. Here, we have developed an effective wheat genome editing pipeline. We used next-generation sequencing (NGS) data to estimate genome editing efficiency of many gRNAs using the wheat protoplast assay and choose the most efficient gRNAs for plant transformation. We successfully applied this pipeline to five wheat orthologs of the rice yield component genes that have been identified previously. We obtained edited plants for all these genes and validated the effect of the mutations in TaGW7 on wheat traits, which showed trends similar to those in rice. These results suggest that transferring discoveries made in rice to improve wheat is a feasible and effective strategy to accelerate breeding.
Keywords: Gene editing; CRISPR/Cas9; Wheat; Seed size; Seed shape; TaGW7